Pemikiran tentang Kota Allah dan Kota Dunia: Analisis Kritis terhadap Demokrasi dan Kapitalisme serta Relevansinya dengan Sistem Demokrasi Indonesia - Oliverensius Ngatamri; Fransiskus Erick Saputra Pantur; Fransiskus Sandriano (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
The book on the City of God and the City of Man is a masterpiece by St. Augustine that is very influential in the history of philosophy and theology. This book contains the background of Augustine's philosophical and theological reflections on the accusation of the destruction of the Roman Empire against Christianity. The City of God described in Augustine's perspective is a city that prioritizes love for God. While the City of Man is a city that reflects self-love. The implications of both types of cities in Augustine's perspective are very relevant to be discussed in the discourse on the concept of statehood. This paper also aims to analyze the relationship between democracy and capitalism in the perspective of Augustine of Hippo's thought, especially through the concept of civitas Dei (City of God) and civitas terrena (World City). This study uses a qualitative method with a library research approach. The results of this study show that democracy and capitalism, although providing space for freedom, are vulnerable to deviations when not guided by the correct moral orientation. In light of Augustine's thought, the crisis in modern democracy such as; Money politics, media manipulation, and anarchic demonstrations reflect the dominance of self-love (amor sui) that characterizes the civitas terrena. Therefore, democracy can only operate fairly if it is rooted in moral values ​​that lead to the common good (Bonum communae).